"Personally, I like it. Professionally, it does not make sense" – social work students in South Africa and Sweden making sense of internationalization. Issue 5 (5th December 2022) - Wilińska, Monika; Bülow, Pia Helena; Keet, Annaline; Esau, Merlene Christobelle
ABSTRACT: Internationalization of higher education and international social work are commonly accepted as positive developments. However, the quest for creating international knowledge and programmes is not free from difficulties. In this article, we problematize the process of internationalizing social work programs through the perspective of social work students. With two study sites, one in Sweden and one in South Africa, we discuss the meaning and challenges associated with internationalization by drawing on the emerging disparity between personal and professional points of view. We conclude by reflecting upon the role of social work educators in translating the ideas of internationalization to the future social workers.